Expounding the role of tick in Africa swine fever virus transmission and seeking effective prevention measures: A review - Lv, Tianbao; Xie, Xufeng; Song, Ning; Zhang, Shilei; Ding, Yue; Liu, Kun; Diao, Luteng; Chen, Xi; Jiang, Shuang; Li, Tiger; Zhang, Wenlong; Cao, Yongguo (Frontiers in Immunology, 2022)
African swine fever (ASF), a highly contagious deadly infectious disease, has caused huge economic losses to animal husbandry with a 100% mortality rate of the most acute and acute infection, which is listed as a legally reported animal disease by the World Organization for Animal Health (OIE). African swine fever virus (ASFV) is the causative agent of ASF, which is the only member of the Asfarviridae family. Ornithodoros soft ticks play an important role in ASFV transmission by active biological or mechanical transmission or by passive transport or ingestion, particularly in Africa, Europe, and the United States. First, this review summarized recent reports on (1) tick species capable of transmitting ASFV, (2) the importance of ticks in the transmission and epidemiologic cycle of ASFV, (3) the ASFV strains of tick transmission, to provide a detailed description of tick-borne ASFV. Second, the dynamics of tick infection with ASFV and the tick-induced immune suppression were further elaborated to explain how ticks spread ASFV. Thirdly, the development of the anti-tick vaccine was summarized, and the prospect of the anti-tick vaccine was recapitulated. Then, the marked attenuated vaccine, ASFV-G-ΔI177L, was compared with those of the anti-tick vaccine, to represent potential therapeutic or strategies to combat ASF.